Flow cytometry as a potential method of measuring bacterial viability in probiotic products: A review. (August 2018) - Wilkinson, Martin G.
Highlights: A review of flow cytometry for monitoring probiotic culture viability was undertaken. Flow cytometry had good correlation with plate counts for concentrated fresh cultures. Sample clean up steps are extremely important to achieve optimal resolution. Flow cytometry generates multi-parametric data not always reflecting plate counts. Regulatory definitions of cell viability and cell vitality needs clarification.